Fabrication of the suspension test set up / Mohd Zaki Bahrom, Kamarul Fiqri Ahmad and Mohd Shahar Abdul Aziz - Bahrom, Mohd Zaki; Ahmad, Kamarul Fiqri; Abdul Aziz, Mohd Shahar (2000)
The tittle of our final project is "Fabrication of a Suspension Test Set up". The purpose of this study shall be concerning with the uses of different shock absorbers in motorcycle suspension system. Generally, in this project we fabricated the test set-up for testing suspension systems of motorcycles with different shock absorbers and loads while they are in operation. In future, students working in this test set-up will be able to find the performance of shock absorber by using different springs and different oils. By this research, we can know the ability of shock absorber by following the duration of uses and how much capacity of load can loading at motorcycle.